Molecular-level insight of hindered phenol AO-70/nitrile-butadiene rubber damping composites through a combination of a molecular dynamics simulation and experimental method. Issue 89 (9th September 2016) - Zhao, Xiuying; Zhang, Geng; Lu, Feng; Zhang, Liqun; Wu, Sizhu
Abstract : The damping properties of AO-70/NBR composites get a noteworthy increase with the introduction of AO-70—max tan δ increased by 66.9%. Abstract : Through a combination of a molecular dynamics (MD) simulation and experimental method, in this work we have methodically expatiated the essential mechanism of the observably enhanced damping performance of nitrile-butadiene rubber (NBR) ascribed to the introduction of hindered phenol AO-70. The computed results revealed that four types of hydrogen bonds (H-bonds), namely, type A (AO-70) –OH⋯NC– (NBR), type B (AO-70) –OH⋯OC– (AO-70), and type C (AO-70) –OH⋯OH– (AO-70), type D (AO-70) –OH⋯O–C– (AO-70) were formed in the AO-70/NBR composites, where type A was the most stable. Meanwhile, the AO-70/NBR composite with AO-70 content of 109 phr had the largest number of H-bonds, highest binding energy, and smallest fractional free volume (FFV), demonstrating a good compatibility between NBR and AO-70 and the best damping property of the composites. The experimental results were highly consistent with the MD simulation results, which means the combining methods can provide a new attempt for the design of optimum damping materials.